Poverty Determination Analysis In Seventeen Districts With The Highest Poverty Rate In East Java - Moh. Faizin; Muh. Najib Amril Huda (Niqosiya: Journal of Economics and Business Research, 2024)
Poverty has, until now, become an endless issue when discussed. This study aims to test and analyze several macroeconomic variables in the form of GRDP, open unemployment, minimum wage, and human development index about the poverty rate in seventeen districts in East Java with the highest poverty rate. By using panel data regression analysis and Eviews as the analysis tool, the results showed that partially only HDI had a significant effect on poverty. In contrast, the other three dependent variables showed the opposite result. The regression results also showed that the influence of four variables simultaneously affected poverty. The results of this research can be a reference in determining government policies at the central and regional levels to reduce the rate of poverty in each region.